Vegetation growth improvement Inadequately represents the ecological restoration of the Populus euphratica forests in Xinjiang, China - Xuefei Guo; Junli Li; Jiudan Zhang; Chunxia Wei; Zhijun Li (Ecological Indicators)
The Populus euphratica Oliv (P. euphratica) is a representative tree species in the riparian forests of arid regions, which acts as a barrier to prevent desert invasion and provides various ecosystem services for biodiversity conservation and ecological security. However, the community of P. euphratica has experienced significant shrinkage and ecological degradation over the past centuries due to natural and anthropogenic factors, particularly in the arid regions of Xinjiang, China. Monitoring the health of these forests is crucial for understanding forest succession and ecosystem restoration. This study used time-series NDVI data from Landsat imagery and fieldwork investigations to monitor vegetation growth and stand age structures of P. euphratica forests in Xinjiang and explore the driving factors of these changes. The result showed that the P. euphratica forests in Xinjiang had experienced vegetation recovery over the last 30 years, with 61 % showing significant recovery and 9 % showing slight recovery. Due to higher precipitation, the vegetation growth rates in northern Xinjiang are more significant than those in southern Xinjiang. However, the increasing vegetation growth of the P. euphratica forests is primarily due to the flourishing of undergrowth vegetation rather than the P. euphratica trees. The P. euphratica forests in northern Xinjiang have ageing population structures, posing challenges for natural forest regeneration. On the other hand, in southern Xinjiang, the P. euphratica forests in flood inundation areas due to the Ecological Water Transfer Project (EWTP) have more significant growth rates and appropriate age structures. The growth rates of these forests were positively correlated with the annual water transfer accumulation but negatively correlated with the distance from the river channels. Therefore, flood inundation is crucial for forest restoration and regeneration. More artificial water supplement measures, such as expanding ecological water transfer areas and increasing water canal densities, will be considered for the ecological restoration of the P. euphratica forests.